The Loneliness and Emotional Levels of the Elderly: Correlation Study in Karang Werda Peer Group - Yunnita, Sisma Yessi; Rasni, Hanny; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2024)
Introduction: The elderly are a vulnerable group who experience the aging process, physical and psychological health problems. Prolonged loneliness results in decreased immunity, sleep disturbances, emotional mental disorders, depression, and even suicide. Purpose: This study was to analyze the correlation between loneliness and the emotional level of the elderly in Karang Werda, Balung District, Jember Regency. Methods: This study used quantitative research methods with a correlational descriptive approach and a cross sectional design. The sample is 108 elderly with the Stratified Random Sampling technique. Loneliness data collection using the UCLA Loneliness Scale Version 3 and emotional levels using the Emotion Regulation Questionnaire (ERQ). Results: It was found that (79%) of the elderly experienced mild loneliness and (79%) had a good emotional level. The correlation between loneliness and emotional level result obtained (p= 0,003, r= -0.202). Conclusion: There is a correlation between loneliness and the emotional level of the elderly in Karang Werda, Balung District, Jember Regency. It is hoped that the elderly can relate well to the surrounding environment and actively participate in group activities. Nurses must carry out routine psychological care for the elderly and provide appropriate interventions.